The Study of Satisfaction with the Selection of Netflix Original Movies and Series that affects the Decision to become a Member of Netflix Thailand - Patikhom, Nunthicha; Singlumpong, Ongart (Siam Communication Review, 2025)
This study aims to: 1) examine the demographic differences among Netflix Thailand subscribers, 2) investigate the decision-making process behind becoming a Netflix Thailand member, and 3) explore the influence of satisfaction with Netflix Original movies and series on the decision to subscribe. The research employed a quantitative, exploratory approach using purposive sampling through an online questionnaire. The findings indicate that most respondents were female, aged between 31–40 years, held a bachelor's degree, and worked in the private sector. Interest in Netflix Original content—particularly new releases, large-scale productions, and high-quality content—significantly influenced both initial subscriptions and continued membership. Additionally, users considered value for money through comparisons with other streaming platforms, ease of access via multiple devices, reasonable pricing, and social media promotions. These factors collectively contributed to a high tendency for long-term subscription retention.